Wavelet transform in stock prices forecasting and related financial data - Harun, Hanani Farhah; Abdullah, Mimi Hafizah (AIP Publishing, 2023)
The aim of this systematic review is to give attention towards the use of wavelet transform in denoising financial time series. This is important to deliver an accurate option pricing for the use of investors or other market practitioners. In this paper, there are many areas of application where researchers employ wavelet transform in time series analysis. Different wavelet transforms with various methodologies have been recorded; either based on the stand-alone wavelet transform function or its integration with other models. The lack of use of wavelet transform in option-implied information in facilitating market practitioners in improving the option valuation accuracy has been identified to be one of promising avenue to be explored, based on the reviews.